Authorship and the Boundaries of Copyright: Ideas, Expressions, and Functions in Yoga, Choreography, and Other Works - Buccafusco, Christopher (The Columbia Journal of Law & the Arts, 2016)
One man created a series of bodily movements to be performed with musical accompaniment by a group of people. Another man created a different series of bodily movements to be performed with different musical accompaniment also by a group of people. The first man was Vaslav Nijinsky, and the creation was the choreography for the ballet Le Sacré du Printemps. The second man was Richard Simmons, and the creation was Sweatin’ to the Oldies. Is there a difference between these creations for purposes of their copyrightability? If so, where does it lie? Now consider a third creator, Alice. After years of study, research, and practice, Alice develops an original and creative series of physical, bodily movements which, when performed, will produce particular thoughts and feelings in the performer’s mind. In addition, performing the sequence of movements will reduce the performer’s blood pressure and minimize her risk of injury. Finally, Alice intends that some people will see the sequence performed and that they will think that it is graceful and reminiscent of various animals in motion. To what extent, if any, has Alice created a copyrightable work of authorship when she describes the series of movements in text and images? According to the Ninth Circuit’s opinion in Bikram’s Yoga College of India v. Evolation Yoga, the answer is likely none. 3 The court ruled that the series of yoga poses developed by the plaintiff, Bikram Choudhury, was “an idea, process, or system,” and thus, ineligible for copyright protection. This Essay uses the Ninth Circuit’s opinion as an opportunity to analyze the nature of copyrightable authorship and the mechanisms that copyright law uses to screen out uncopyrightable content from copyrightable works. I argue that although the court likely reached the right result in Bikram, it did so in a confused and poorly supported manner. Moreover, the court’s analysis would likely result in a determination that my hypothetical Alice also could not receive copyright protection, even though a proper understanding of copyright doctrine might lead to a different result. I show how courts should deal with situations like these, in which potentially copyrightable expression is combined with unprotectable functional elements. Essential to these questions is an understanding of the nature of copyrightable authorship.